2018
DOI: 10.1080/15384047.2018.1480888
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of circRNA_NEK6 targeting miR-370-3p in the proliferation and invasion of thyroid cancer via Wnt signaling pathway

Abstract: CircNEK6 promoted the progression of thyroid cancer through up-regulating FZD8 and activating Wnt signaling pathway by targeting miR-370-3p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 31 publications
5
76
0
Order By: Relevance
“…In recent years, altered expression and activity of NEK6 were associated with several types of cancer, such as liver [139], prostate [140], gastric [141][142][143], colorectal [144,145], breast [146], serous epithelial ovarian [147], thyroid [148], and retinoblastoma cancers [149]. In addition, inflammation-based diseases, such as ulcerative colitis, have also been linked to NEK6 [28].…”
Section: Nek6mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, altered expression and activity of NEK6 were associated with several types of cancer, such as liver [139], prostate [140], gastric [141][142][143], colorectal [144,145], breast [146], serous epithelial ovarian [147], thyroid [148], and retinoblastoma cancers [149]. In addition, inflammation-based diseases, such as ulcerative colitis, have also been linked to NEK6 [28].…”
Section: Nek6mentioning
confidence: 99%
“…The circular RNA of NEK6 may increase the expression of Frizzled class receptor 8 (FZD8), a constituent of the Wnt signaling pathway, since it binds and inhibits mRNA-370-3p, a tumor suppressor. Full understanding of circular RNA functions will be critical to verify their role in cancer, and more studies aimed at development of new treatments for cancer are needed [148].…”
Section: Nek6mentioning
confidence: 99%
“…In thyroid cancer, circNEK6 is a competing endogenous RNA of FZD8 that absorbs miR-370-3p, resulting in the activation of the Wnt/β-catenin signaling pathway. The upregulation of circNEK6 enhances the expression of c-myc and CCD1, whereas silencing FZD8 abrogates their expression [75]. Chen et al demonstrated that hsa_circ_0000177 is a miR-638 sponge that targets FZD7.…”
Section: Wnt Pathway-related Circrnasmentioning
confidence: 99%
“…Increasing evidence indicates that circRNAs are preferentially located and function in the cytoplasm, and they function as microRNA (miRNA) sponges to affect translation or bind directly to proteins regulating the protein function and localization . In this study, bioinformatics analysis identified miR‐760 and SOCS3 as the downstream targets of hsa_circ_0007874 (Figure A).…”
Section: Resultsmentioning
confidence: 82%